The Combining Ability for Grain Yield and Some Related Characteristics in Rice (Oryza sativa L.) Under Normal and Water Stress Conditions - Abd El-Aty, Mohamed S.; Katta, Youssef S.; El-Abd, Abd El Moaty B.; Mahmoud, Samiha M.; Ibrahim, Omar M.; Eweda, Mohamed A.; El-Saadony, Mohamed T.; AbuQamar, Synan F.; El-Tarabily, Khaled A.; El-Tahan, Amira M. (Frontiers in Plant Science, 2022)
Drought is considered a major threat to rice production. The objective of this study was to determine the impacts of drought stress on the estimates of heterosis and combining ability of rice genotypes for the number of days to 50% heading, plant height, number of panicles per plant, panicle length, number of filled grains per panicle and grain yield per plant. Field experiments in the Rice Research and Training Center, Kafr Elsheikh, Egypt, during the rice growing seasons of 2018 and 2019 were conducted. Eight rice genotypes (Giza178, Giza179, Sakha106, Sakha107, Sakha108, WAB1573, NERICA4 and IET1444) were crossed in a half diallel cross in the 2018 season, providing a wide range of variability for numerous agronomic traits and drought tolerance measurements. In 2019, these parents and their 28 F1 crosses were produced in a three-replication randomized complete block design under normal and water stress conditions. The results demonstrate significant differences across the studied genotypes under normal and water stress conditions. Under both conditions, Sakha 107 was the best general combiner for earliness and short stature. Giza 179 and Sakha 108 were the best general combiners for grain yield per plant and one or more of its characteristics. Furthermore, in both normal and water stress conditions, Giza 179 displayed the highest general combining ability impacts for all evaluated attributes. Under normal and water stress circumstances, the cross (Giza179 × Sakha107) demonstrated highly substantial desirable specific combining ability effects on all examined traits, suggesting that it might be considered for use in rice hybrid breeding programs. Therefore, we recommend considering these important indirect selection criteria for improving rice grain yield under drought conditions.